2020
DOI: 10.1126/sciadv.abb5223
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoscale metal-organic frameworks for x-ray activated in situ cancer vaccination

Abstract: Cancer vaccines have been actively pursued to bolster antitumor immunity. Here, we designed nanoscale metal-organic frameworks (nMOFs) as locally activable immunotherapeutics to release danger-associated molecular patterns (DAMPs) and tumor antigens and deliver pathogen-associated molecular patterns (PAMPs) for in situ personalized cancer vaccination. When activated by x-rays, nMOFs effectively generate reactive oxygen species to release DAMPs and tumor antigens while delivering CpG oligodeoxynucleotides as PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…[33] Studies have shown that stimulators of interferon gene agonists are also members of the candidate vaccine adjuvant library. [34,35] As the most studied PRR, there have been a variety of TLR agonists as immunostimulatory adjuvants, [36] including the TLR4 agonist monophosphoryl lipid A, [37,38] the TLR9 agonist cytosine phosphodiester guanine (CpG) oligodeoxynucleotide (ODN), [39] and the TLR7/8 agonist imiquimod. [40] The combined use of these adjuvants may produce a synergistic effect.…”
Section: Immune Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Studies have shown that stimulators of interferon gene agonists are also members of the candidate vaccine adjuvant library. [34,35] As the most studied PRR, there have been a variety of TLR agonists as immunostimulatory adjuvants, [36] including the TLR4 agonist monophosphoryl lipid A, [37,38] the TLR9 agonist cytosine phosphodiester guanine (CpG) oligodeoxynucleotide (ODN), [39] and the TLR7/8 agonist imiquimod. [40] The combined use of these adjuvants may produce a synergistic effect.…”
Section: Immune Adjuvantsmentioning
confidence: 99%
“…By analyzing these physical and chemical properties, nanocarriers that can accurately deliver antigens to LNs and DCs were designed. OVA, Imiquimod, MPL 260 B16-OVA [40] OVA, imidazoquinoline-based esters 156 ± 26 B16-OVA [45] B16-F10 membrane, CpG 120 B16-F10 [82] OVA, HCQ 225.90 ± 2.65 E.G7-OVA [ 108] MPG ΔNLS -OVA 249.5 ± 13.5 E.G7-OVA [ 110] PEG-b-PAGE-b-PLGA OVA 196.5 ± 3.8 Caco-2 [51] PEG-PE, PSA Trp2, CpG 30 B16-F10 [66] PCL-PEI, PCL-PEG Trp2, CpG 80 B16-OVA [86] 3s-PLGA-PO-PEG, PEI OVA 220.4 ± 1.8 ∖ [87] COOH-Pluronic F127/PEOz-PLA OVA, CL264 50 E.G7-OVA [91] PEG-b-PC7A OVA 20-50 B16-OVA [94] DGBA OVA, CpG 105.7-167.7 B16-OVA [95] PLGA, NH 4 HCO 3 OVA 893.63 ± 7.93 B3Z [ 101] pPAA OVA, 𝛼-GalCer 78 B16-OVA [ 106] PLGA @Man-RBC hgp100 25-33 , MPL 149.2 ± 0.6 B16-F10 [ 114] PLH-PEG OVA 124.0 ± 4.780 B16 [ 116] F-PEI OVA 157-250 B16-OVA [ 129] Lipid nanocarrier DP7-C-modified liposome DOTAP, neoantigen mRNA, DP7-C 130.45 ± 9.32 LL2 [41] PLGA-core/lipid-shell hybrid NP mRNA codingOVA, gardiquimod 400 B16-OVA [50] Lipid-PEG NP mRNA coding OVA, G0-C14, C16-R848 137 ± 2.8 E.G7-OVA, RM1-OVA [53] triMN-liposome mRNA coding MART-1 180 TC1, B16, E.G7-OVA [54] Mannose-coated liposome TRP2 180-188 , CpG 102 ± 9 B16-OVA [55] Cationic lipid-assisted NP mRNA coding OVA, MPLA 110 E.G7-OVA [67] Cationic lipid-hybrid NP OVA 236.4 ± 13.2 ∖ [89] Lipid-polymer hybrid NP OVA, MPLA, IMQ 220.77 ± 3.23 EG7-OVA [90] Inorganic nanocarriers nMOF(Hf-DBB F -Ir) CpG 100 MC38, B16-F10, Panc02 [39] GNP OVA 22-33 EG7-OVA [62] XL-MSNs OVA, CpG 100-200 B16-OVA [79] Man-MWCNTs OVA ∖ ∖ [81] MOF(ZIF-8) OVA, CpG 200 ∖ [96] MOF(ZANP) OVA, aluminum, CpG 80 EG7-OVA [97] MS@MOF OVA, PolyIC 100 EG7-OVA [98] CaCO 3 OVA 500 EG7-OVA…”
Section: The Design Of Precision-delivery Nanocarriersmentioning
confidence: 99%
“…Personalized TCV in situ represents a promising strategy to overcome tumor heterogeneity by inducing autologous whole tumor antigens release [ 10 12 ]. Up to now, a variety of immuno-stimulatory treatments for development of TCV, such as oncolytic viruses [ 13 , 14 ], radiotherapy [ 15 , 16 ], chemotherapy [ 17 ] and phototherapy [ 18 , 19 ], have been reported to generate tumor-associated antigens in situ by inducing immunogenic cell death (ICD) [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is recent interest in the investigation of small molecule compounds isolated from traditional medicinal plants and heavy metal-based nanoparticles as radiosensitizers. [25][26][27][28] Recent reports have suggested that micheliolide (MCL), a small molecule originally isolated from Michelia compressa and champaca shows anti-inflammatory and anticancer properties. [29][30][31] MCL is a sesquiterpene lactone, a class of natural products containing an 𝛼-methylene-𝛾-lactone moiety and an epoxide group which can interact with proteins to exert a diverse range of biological and pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%